Next Generation Transit Survey (NGTS). Issue Volume 8:Issue S299(2013) (6th January 2014) - Wheatley, Peter J.; Pollacco, Don L.; Queloz, Didier; Rauer, Heike; Watson, Christopher A.; West, Richard G.; Chazelas, Bruno; Louden, Tom M.; Bannister, Nigel; Bento, Joao; Burleigh, Matthew; Cabrera, Juan; et al.
Abstract: The Next Generation Transit Survey (NGTS) is a new ground-based survey for transiting exoplanets. Our primary goal is to find the first statistically-significant sample of Neptunes and super-Earths that are bright enough for radial velocity confirmation. By measuring precise masses and radii we will constrain the bulk composition and internal structure of planets that span the transition between the gas giants and terrestrial planets. Our brightest exoplanets will also be suitable for atmospheric characterisation with large facilities such as the VLT, JWST and the E-ELT. NGTS construction began in June 2013, and the survey is due to commence in 2014.